2018
DOI: 10.18632/oncotarget.24761
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a-induced cell migration is associated with the aggressiveness of estrogen receptor-positive breast cancer

Abstract: Elevated expression of Wnt5a is associated with malignancy, cell invasion, and metastasis. The role of Wnt5a expression in breast cancer remains elusive. We investigated the significance of Wnt5a expression in breast cancer. The relationship between Wnt5a expression and clinicopathologic factors was assessed in invasive breast cancer (n = 178) resected at Hiroshima University Hospital between January 2011 and February 2014. Wnt5a was expressed in 69 of 178 cases (39%) of invasive breast cancer and correlated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
0
26
2
Order By: Relevance
“…Wnt family member 5A (WNT5A) is implicated in oncogenesis and several developmental processes. According to previous studies, WNT5A promote multiple cellular processes of cancers [33][34][35][36] . Accordingly, it was confirmed by our paper that PITPNA-AS1 modulated WNT5A expression by targeting miR-876-5p.…”
Section: Discussionmentioning
confidence: 91%
“…Wnt family member 5A (WNT5A) is implicated in oncogenesis and several developmental processes. According to previous studies, WNT5A promote multiple cellular processes of cancers [33][34][35][36] . Accordingly, it was confirmed by our paper that PITPNA-AS1 modulated WNT5A expression by targeting miR-876-5p.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, recent work has demonstrated a role for two distinct Wnt5a isoforms, Wnt5a-short and Wnt5a-long, in colorectal cancer progression and active Wnt signalling (Huang et al 2017). It is unknown what isoform Foxy-5 is based upon, and prudence is required, particularly for breast cancer patients where an increase of Wnt5a and ROR receptors has been shown to have oncogenic properties (Henry et al 2015, Han et al 2018, Kobayashi et al 2018.…”
Section: :12mentioning
confidence: 99%
“…Previous studies have demonstrated that Wnt5a has a dual effect on the progression of various types of human cancer [10], indicating that this pathway is particularly dependent on the cellular context [7]. Wnt5a is considered to have a tumor-suppressive function in neuroblastoma [11], leukemia [12], ductal breast carcinomas [13], ER-positive breast cancer [14], colorectal cancer [15], and thyroid cancer [16]. On the other hand, a protumorigenic role for Wnt5a has been shown for T-cell leukemia [17], melanoma [18], gastric cancer [19], non-small-cell lung cancer [20], pancreatic cancer [21], and prostate cancer [22].…”
Section: Introductionmentioning
confidence: 99%